The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1109/lpt.2013.2280700
|View full text |Cite
|
Sign up to set email alerts
|

VCSEL-Based Optical Frequency Combs: Toward Efficient Single-Device Comb Generation

Abstract: . Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.Serrano, A.R.C.; de Dios Fernandez, C.; Cano, E.P.; Ortsiefer, M.; Meissner, P.; Acedo, P., "VCSEL-Based Optical Frequency Combs: Toward Efficient Single-Device Comb Generation", IEEe Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A degradation of the phase noise of this beat tone is associated to an overall loss of coherence among the optical modes. In [7] we found that the phase noise of the VCSEL based GS-OFCG is similar to that of the reference signal. In the present work (Figure 4) we have evaluated EO and Combined techniques.…”
Section: Coherence Of the Modes Of The Combmentioning
confidence: 68%
See 3 more Smart Citations
“…A degradation of the phase noise of this beat tone is associated to an overall loss of coherence among the optical modes. In [7] we found that the phase noise of the VCSEL based GS-OFCG is similar to that of the reference signal. In the present work (Figure 4) we have evaluated EO and Combined techniques.…”
Section: Coherence Of the Modes Of The Combmentioning
confidence: 68%
“…The use of edge emitting technologies such as Fabry-Perot [10], Distributed Feedback Bragg lasers or Discrete Mode [11] has been recently reported. In this sense, our previous work [7] shows that the use of high performance Vertical Cavity Surface Emitting Lasers (VCSEL) permits the generation of an enhanced comb, record in energy efficiency and optical span. This result drives our interest to study the possibilities of this technology as the core of an OFCG that could meet the requirements detailed before.…”
Section: T He Interest Optical Frequency Comb Generators (Ofcg)mentioning
confidence: 99%
See 2 more Smart Citations
“…Possibilities if simplifying the expansion was also discussed. In 2013, A. R. Criado et al [215] reported on the use of VCSEL for gain switched comb generation. The authors reported on the generation of a comb exhibiting 20 tones within a 3 dB ripple at a FSR of 6.25 GHz.…”
Section: C-bandmentioning
confidence: 99%